EFEKTIVITAS TEKNIK RELAKSASI NAFAS DALAM TERHADAP PENURUNAN NYERI HAID (DISMENORE) PADA SISWI - Ibrahim ,; Andika Herlina Marda Prawata; WEZA YETIKA S.Kep (Stikes Syedza Saintika Padang, 2020)
Painfull Menstruation (dysmenorrhea) is a pelvic pain that occurs before menstruation or during the period. In Indonesia is estimated around 55% of women of reproductive age who are tormented by pain during menstruation. The purpose of this study to determine the effectiveness of deep breathing relaxtion technique to decrease painful menstruation (dysmenorrhea) of female students in class X and XI senior high school negeri 3 sungai penuh.Type of research this pre exsperiment with desain one-group pre test-post test of which execute in senior high school negeri 3 sungai penuh in January- July 2020. Population in this study were all students of class X and XI senior high school negeri 3 sungai penuh which amount to 60 people, technique sampel use metode purposive.Was collecting use kuesioner by enquette. Data in process in manual with step editing, codyng, entry, tabulating and cleaning and analysis in univariat use descriptive statistic and analysis of bivariate use to test t-test dependent with storey: level 95% (α=0,05)Of research concluded there is the effectiveness of deep breathing relaxation tecnique to decrease painful menstruation (dysmenorrhea) of female students in class X and XI senior high school negeri 3 sungai penuh, it is expected to head master the high school negeri 3 sungai penuh stream to further optimize in an effort to increase the knowledge of pain reduction efforts mainly on menstrual pain as wellas working with health workers in the program on the initial actions cope with menstrual pain.